1978
DOI: 10.1002/1097-0142(197805)41:5<2018::aid-cncr2820410550>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Sunlight as a risk factor of malignant melanoma of the skin

Abstract: The series of cutaneous melanoma compiled by the Finnish Cancer Registry, a total of 2501 cases covering all tumors diagnosed in Finland in 1953-1973, was analysed. The age adjusted incidence was equal in both sexes (about 3.5/105 in the 1970s). The risk more than doubled during the study period. The most common locations of melanoma in males were the trunk (48%) and lower limbs (17%), and in females the lower limbs (36%) and the trunk (28%).The age adjusted incidence rates were higher in urban areas than in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
30
1
1

Year Published

1980
1980
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 16 publications
4
30
1
1
Order By: Relevance
“…This study of 37 population-based cancer registries has confirmed earlier reports (Lee & Yongehaiyudha, 1971;Magnus, 1973;Teppo et al, 1978) that about 75% of melanomas occur on the relatively unexposed sites of the limbs and body. The site distribution of malignant melanoma would appear, as Teppo et al have suggested, to be at variance with the supposed role of UV as the major aetiological factor.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This study of 37 population-based cancer registries has confirmed earlier reports (Lee & Yongehaiyudha, 1971;Magnus, 1973;Teppo et al, 1978) that about 75% of melanomas occur on the relatively unexposed sites of the limbs and body. The site distribution of malignant melanoma would appear, as Teppo et al have suggested, to be at variance with the supposed role of UV as the major aetiological factor.…”
Section: Discussionsupporting
confidence: 89%
“…The important point about these two sites is that the differences in exposure are not marked and the differences in incidence small. Similar sex differences have been reported previously in isolated studies (Lee & Yongehaiyudha, 1971;Magnus, 1973;Teppo et al, 1978). An important feature of the argument that the site distribution of melanoma does not accord with exposure is the comparison with the non-melanoma skin tumours.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…THE INCIDENCE of malignant melanoma is rising rapidly (Elwood & Lee, 1975;Lee, 1976;Magnus, 1977;Teppo et al, 1978;Malec & Eklund, 1978;SoodalterToman et al, 1979) and, although prognosis is improving (End Results, 1976), this is not keeping pace, and the death rate is rising at about 3 % a year (Lee et al, 1979). The reason for these changes is unknown.…”
mentioning
confidence: 99%